A nonsense mutation in BRCA1 gene in a Vietnamese patient with breast cancer - Tung, Nguyen Van; Huan, Le Duc; Hien, Do Minh; Mai, Bui Bich; Phuong, Pham Cam; Lien, Nguyen Thi Kim; Hanh, Ha Hong; Hien, Nguyen Thanh; Hoang, Nguyen Huy (Vietnam Journal of Biotechnology, 2023)
Breast cancer is the most frequent female cancer, and it is increasing at an alarming rate. The typical symptom of breast cancer is breast lumps or swellings, though they can also develop close to the breast or under the arm. Breast cancer usually spreads to distant organs such as the bone, liver, lungs, and brain. Approximately 95% of breast cancer patients who arrive with the early-stage disease show no macroscopic signs of metastases. Although it is possible to reduce some breast cancer risks through prevention, the majority of patients in low-income countries are detected at a late stage. Because of this, even though current therapy is improving, early diagnosis is still crucial for improving the quality of treatment and the survival rate. Sex, age, family history, and an unhealthy lifestyle are some of the risk factors that may increase the chances of getting this disease. Familial or hereditary breast cancer accounts for 10% of breast cancers. Mutations in the BRCA1 and BRCA2 genes were responsible for 50% of all familial or hereditary breast cancer cases. In this research, mutations in a Vietnamese patient with familial breast cancer were analyzed using whole exome sequencing. As a result, 17 variants have been reported in the ClinVar database as “germline mutations” in familial breast cancer were detected. Of these, a heterozygous nonsense mutation c.5314C>T (p.R1772X) in the BRCA1 gene was identified as the genetic cause of this case. This mutation has been previously reported as pathogenic in the ClinVar database (ClinVar variation ID: 55480). Our results provide insight into the genetic causes of breast cancer as well as support the genetics diagnosis of familial breast cancer.